2012
DOI: 10.3109/0167482x.2011.652996
|View full text |Cite
|
Sign up to set email alerts
|

Perceived control and maternal satisfaction with childbirth: a measure development study

Abstract: The purpose of this study was to develop and validate two instruments: one to assess patient perceptions of control of the childbirth environment and the other, global satisfaction with the childbirth experience. Participants were 187 women recruited from obstetric clinics, breast-feeding support groups and online who had given birth in the past 4 months. Scale development involved item construction, exploratory factor analysis (EFA) of the Perceived Control in Childbirth Scale (PCCh), confirmatory factor anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 53 publications
3
35
0
3
Order By: Relevance
“…Stevens, Wallston, and Hamilton (2012) found that intrapartum supportive care enhances perceived control. Consistent with those findings, this study revealed that intrapartum supportive care improves perceived internal and external control during birth.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Stevens, Wallston, and Hamilton (2012) found that intrapartum supportive care enhances perceived control. Consistent with those findings, this study revealed that intrapartum supportive care improves perceived internal and external control during birth.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with those findings, this study revealed that intrapartum supportive care improves perceived internal and external control during birth. Perceived control during birth involves coping with pain, exhibiting the behavior expected of the self-birth, making decisions, accessing medical information, self-competency, and emotional status (Elmir, Schmied, Wilkes, & Jackson, 2010;Goodall, McVittie, & Magill, 2009;Stevens et al, 2012). Perceived control during childbirth has been associated with emotions felt during the birth process (Elmir et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the complementary therapy is used to release the tension and relax the muscles of pregnant women with intense pain. Interventions to relieve sever pain often includes immersion in water (7), acupuncture and acupressure (8), transcutaneous electrical nerve stimulation (TENS) (9), breathing techniques, yoga (10), hypnosis (11), physical and emotional support for coping with pain (12, 13), music therapy (14), listening to Quran, and massage therapy (15). Many researches have been already investigating on these interventions.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized higher scores on the LADY-X sum score for (1) [28,31,32], (4) no transfer during labor vs. transfer during labor [28,33], (5) control vs. no control over pain medication [28,30], (6) no complications vs. complications at or right after the birth concerning mother [34], (7) no complications vs. complications concerning the child at or right after the birth [34], and (8) experiencing a high vs. a low level of control [28,30]. The level of control was measured by the LAS and dichotomized by a median split.…”
Section: Construct Validitymentioning
confidence: 99%